Chaetoceros gracilis AS A BIOINDICATOR OF SEDIMENT QUALITY - Rachma Puspitasari; Lestari Lestari (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
Chronic sediment toxicity tests could be used to evaluate the effects of sediment on critical stages in the life of an organism like invertebrate larvae and microalgae. Microalgae play an important role in aquatic ecosystem due to their role as producer in food chain producing organic matter and oxygen through photosynthesis process. This paper aimed to assess sediment quality of Semarang water using chronic sediment toxicity test. Research was conducted by testing 13 sediment samples from Semarang coastal region in August, 2010. Results showed that sediments exposed for 96 hours were still able to stimulate the growth of C. gracilis eventhough the copper concentration was above standard value provided by the CCME. The conclusion from this research was that sediment in Semarang still in good condition and can support growth of C. gracilis as primary producer. Chronic sediment toxicity test using C. gracilis could be combined with heavy metal measurement for sediment quality asessment. Keywords: sediment, bioindicator, diatomae, C. gracilis, chronic toxicity, Semarang